No Modulatory Effects when Stimulating the Right Inferior Frontal Gyrus with Continuous 6 Hz tACS and tRNS on Response Inhibition: A Behavioral Study - Hannah Brauer; Navah Ester Kadish; Anya Pedersen; Michael Siniatchkin; Vera Moliadze (Neural Plasticity)
Response inhibition is the cognitive process required to cancel an intended action. During that process, a “go” reaction is intercepted particularly by the right inferior frontal gyrus (rIFG) and presupplementary motor area (pre-SMA). After the commission of inhibition errors, theta activity (4–8 Hz) is related to the adaption processes. In this study, we intend to examine whether the boosting of theta activity by electrical stimulation over rIFG reduces the number of errors and the reaction times in a response inhibition task (Go/NoGo paradigm) during and after stimulation. 23 healthy right-handed adults participated in the study. In three separate sessions, theta tACS at 6 Hz, transcranial random noise (tRNS) as a second stimulation condition, and sham stimulation were applied for 20 minutes. Based on behavioral data, this study could not show any effects of 6 Hz tACS as well as full spectrum tRNS on response inhibition in any of the conditions. Since many findings support the relevance of the rIFG for response inhibition, this could mean that 6 Hz activity is not important for response inhibition in that structure. Reasons for our null findings could also lie in the stimulation parameters, such as the electrode montage or the stimulation frequency, which are discussed in this article in more detail. Sharing negative findings will have (1) positive impact on future research questions and study design and will improve (2) knowledge acquisition of noninvasive transcranial brain stimulation techniques.